The Role of the Private Sector in Fragile and Conflict-Affected States - Peschka, Mary Porter; Emery, James J. (World Bank, Washington, DC, 2017)
This paper explores how the private sector can positively contribute to peace-building and conflict prevention, and how that positive private sector role can be supported and enhanced. The starting premise recognizes that the private sector exists in all conflict situations and has the potential to both exacerbate and ameliorate conflict, the outcome of which can be greatly affected by appropriate support from external partners. It also posits that a thriving, legal, private sector is essential to development and peace, as it provides livelihoods and growth, while delivering revenue streams in the form of taxes so governments can provide services to their citizens. It also posits that a thriving, legal, private sector is essential to development and peace, as it provides livelihoods and growth, while delivering revenue streams in the form of taxes so governments can provide services to their citizens. This paper discusses and analyzes the role of the private sector in fragile and conflict-affected states, beginning with its role in the conflicts themselves, and in the immediate peace-building and longer-term reconstruction and development phases. The paper acknowledges that the topic of private sector development cuts across political, governance, and security dimensions, as well as a broad range of development themes. It also considers international efforts to support the private sector in fragile and conflict affected settings to date, identifying gaps and making recommendations to address them. The paper does not focus on detailed operational issues or the use of various reform tools.